TERPADU (SIPINTER) TERHADAP KEPUASAN PELANGGAN DI DINAS PENANAMAN MODAL DAN PELAYANAN TERPADU SATU PINTU (DPMPTSP) KABUPATEN TANGERANG - Ricca . Rosalinda; Mach . Murodi; Irvan Arif Kurniawan (UNIVERSITAS ISLAM SYEKH YUSUF, 2019)
This thesis is titled “The Effect of the Application of Integrated Licencing Service Information System (SIPINTER) on Customer Satisfaction in the Investment Service and One-Stop Integrated Service (DPMPTSP) of Tangerang District”. The population in this study is the people who use Application SIPINTER in the Investment Service and One-Stop Integrated Service (DPMPTSP) of Tangerang District amount of 1,337 people from which in the whole population the researchers used 93 people as samples to be tested. This is indicated by the results of testing using the SPSS (Statistical Product and Solution Service) which shows a significant level of 0,000 which means smaller than 0,05 and t count of 7,656 which is greater than t table that is 1,986. This situation shows that Ho was rejected and Ha was accepted, so the hypothesis that the researchers proposed proved correct. The conclusion is that there is a positive and significant effect between the Integrated Licensing Service Information System (SIPINTER) Application on Customer Satisfaction in the Investment Office and the One-Stop Integrated Service (DPMPTSP) of Tangerang District. Keywords: Management Information System, Customer Satisfaction, Licensing